Turcan, Robert. (2018). Tiberio. Buenos Aires: El Ateneo. ISBN: 978-950-020978-6, 304 páginas - Flores, Walter (2018)
Fil: Flores, Walter. Instituto Superior del Profesorado Dr. Joaquín V. González; Argentina